Making an Indonesian National Hero for Lombok: the shifting category of pahlawan nasional - Fogg, K (Taylor and Francis, 2019)
Indonesia’s category of ‘national hero’ or pahlawan nasional has evolved since it first emerged with Indonesian independence. This title went from a popular term for veterans, to a designated national category, to a centrepiece of New Order civil religion. This article chronicles further changes in the post-Suharto era both by a quantitative analysis of the entire pantheon of 179 pahlawan and by the case study of the first national hero for West Nusa Tenggara Province: TGKH M. Zainuddin Abdul Madjid, also known as Tuan Guru Pancor, from the island of Lombok. The category of pahlawan nasional has become both more diverse and more political in the last two decades.